On-demand CO release for amplification of chemotherapy by MOF functionalized magnetic carbon nanoparticles with NIR irradiation. (March 2019) - Yao, Jizong; Liu, Yao; Wang, Jiawen; Jiang, Qin; She, Dejun; Guo, Huishu; Sun, Nianrong; Pang, Zhiqing; Deng, Chunhui; Yang, Wuli; Shen, Shun
Abstract: Carbon monoxide (CO) gas therapy combined with chemotherapy and photothermal therapy (PTT) is a promising treatment mode for malignant tumor. Herein, we firstly reported doxorubicin (DOX) loaded Mn carbonyl modified Fe (Ⅲ)-based nanoMOFs (MIL-100) coated PEGylated magnetic carbon nanoparticles (denoted as MCM@PEG-CO-DOX NPs) as theranostics nanoplatforms for near-infrared (NIR)-responded CO-DOX combination therapy. MIL-100 as a good nanocarrier of DOX with high loading capacity can also chelate the Mn carbonyl after a smart modification. Meanwhile, magnetic carbon core possessed photothermal effect, which can convert the NIR light to heat by an 808 nm laser irradiation, resulting in the on-demand release of CO and DOX. As a result, combining with PTT, MCM@PEG-CO-DOX NPs killed tumor efficiently. Moreover, our synthesized MCM@PEG-CO-DOX NPs were capable of realizing tumor dual-mode imaging including magnetic resonance imaging (MRI) and photoacoustic imaging (PAI).